PENGARUH LITERASI KEUANGAN TERHADAP NIAT BERINVESTASI GENERASI MILENIAL PADA PLATFORM FINTECH BERBASIS EQUITY CROWDFUNDING DENGAN PERSEPSI RISIKO DAN KEPERCAYAAN PADA PLATFORM DAN FUNDRAISER SEBAGAI VARIABEL MEDIASI - M. Niltal Muna; Fitri Ismiyanti (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to analyze the effect of financial literacy on millennials' investment intention on equity crowdfunding-based fintech platforms with risk perception and trust in platforms and fundraisers as mediating variables. This research is a survey with data collection from 200 respondents, millennial generation Indonesian citizens aged 19-35 years, who used non-probability sampling techniques (purposive and snowball sampling). Primary data was collected through a Likert-scale questionnaire, while secondary data came from literature and trusted online databases. The interview method was used with a small number of respondents to obtain additional information. Data analysis involved descriptive statistical techniques and path coefficient analysis to achieve the research objectives. The results showed that financial literacy has a significant positive effect on the intention to invest in equity crowdfunding platforms, but has no significant effect on the perception of investment risk. Trust in the platform and fundraiser contribute positively to investment intention, suggesting the importance of financial literacy in shaping trust and motivation to invest in that context.